2007
DOI: 10.1213/01.ane.0000281156.64133.bd
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique to Reduce Epistaxis and Enhance Navigability During Nasotracheal Intubation

Abstract: The use of esophageal stethoscope-obturated ETTs was effective, and comparable to thermosoftening, in preventing epistaxis associated with nasotracheal intubation. Thermosoftened, obturated ETTs were more effective than simple thermosoftened ETTs in reducing epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 14 publications
2
41
1
Order By: Relevance
“…Currently, thermosoftening [15], the use of vasoconstrictors [6,16] and lubrication are widely used to reduce nasal bleeding following nasotracheal intubation. Several strategies have also been suggested to prevent epistaxis during nasotracheal intubation, including obturation of the tracheal tube [17], and using a nasopharyngeal airway [18] or a red rubber catheter [19] as a guide. The use of an oesophageal stethoscope-obturated tracheal tube was effective in preventing epistaxis associated with nasotracheal intubation by obturating the Murphy-tipped tracheal tube [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, thermosoftening [15], the use of vasoconstrictors [6,16] and lubrication are widely used to reduce nasal bleeding following nasotracheal intubation. Several strategies have also been suggested to prevent epistaxis during nasotracheal intubation, including obturation of the tracheal tube [17], and using a nasopharyngeal airway [18] or a red rubber catheter [19] as a guide. The use of an oesophageal stethoscope-obturated tracheal tube was effective in preventing epistaxis associated with nasotracheal intubation by obturating the Murphy-tipped tracheal tube [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have also been suggested to prevent epistaxis during nasotracheal intubation, including obturation of the tracheal tube [17], and using a nasopharyngeal airway [18] or a red rubber catheter [19] as a guide. The use of an oesophageal stethoscope-obturated tracheal tube was effective in preventing epistaxis associated with nasotracheal intubation by obturating the Murphy-tipped tracheal tube [17]. In Enk et al's study [18], the investigators inserted the tip of the tracheal tube into the trailing end of a red rubber nasopharyngeal airway and the tube was advanced under visual control to the oropharynx, guided by the airway.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, authors describe a decreased incidence of pain reported by adult patients postoperatively following nasal intubation using a pathfinder technique for NTI [17] [18]. Future recommendations would be to conduct postoperative assessments in the pediatric population to correlate findings.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…Vansickle, and Ouanes presented three case reports in which an endotracheal tube introducer or bougie was used to facilitate successful and atraumaticnasal intubation using a Seldinger technique [18]. The authors discussed how the use of a nasal bougie can guide tubes through narrow nasal passages and small pharyngeal spaces without transoral manipulation [19].…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation